2017
DOI: 10.1371/journal.pone.0185102
|View full text |Cite
|
Sign up to set email alerts
|

Novel derivative of Paeonol, Paeononlsilatie sodium, alleviates behavioral damage and hippocampal dendritic injury in Alzheimer's disease concurrent with cofilin1/phosphorylated-cofilin1 and RAC1/CDC42 alterations in rats

Abstract: Alzheimer’s disease (AD) is a typical hippocampal amnesia and the most common senile dementia. Many studies suggest that cognitive impairments are more closely correlated with synaptic loss than the burden of amyloid deposits in AD progression. To date, there is no effective treatment for this disease. Paeonol has been widely employed in traditional Chinese medicine. This compound improves learning behavior in an animal model; however, the mechanism remains unclear. In this study, Paeononlsilatie sodium (Pa), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 126 publications
1
25
0
Order By: Relevance
“…It has been reported that aluminum-mediated cellular injury targets lipids, protein and DNA, which in turn induce oxidative stress, lipid peroxidation and cell injury [11,13,67]. Based on these considerations, in this study AlCl 3 was chosen to induce a model of sporadic AD [2,26,28], with the overall goal of investigating the possible prophylactic effect of VCO in an AlCl 3 -induced AD rat model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that aluminum-mediated cellular injury targets lipids, protein and DNA, which in turn induce oxidative stress, lipid peroxidation and cell injury [11,13,67]. Based on these considerations, in this study AlCl 3 was chosen to induce a model of sporadic AD [2,26,28], with the overall goal of investigating the possible prophylactic effect of VCO in an AlCl 3 -induced AD rat model.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Central crossing, ( 2 ) central time, ( 3 ) peripheral crossing, ( 4 ) peripheral time, and ( 5 ) total crossing ( 25 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The maze was elevated from the ground by 50 cm using stands. The duration of the presence of the rats in the open and enclosed arms was recorded using a digital camera for 5 min ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Rac1/cofilin pathway is inactivated through suppression of the cofilin phosphorylation which causes the loss of dendritic spine in the hippocampus (Yang et al, 2018). The density of dendritic spines and dendritic complexity increase, similar to the change of phosphorylation and redistribution of cofilin-1 in an AD rat model (Han et al, 2017). Cofilin-1 knockdown leads to a decrease number of thin spines and decrease length of dendritic protrusions (Hotulainen et al, 2009).…”
Section: Role Of Cofilin In Synaptic Dysfunctionmentioning
confidence: 96%